From rain-bringer to wealth-giver: Changing forms of the snake in southern African belief systems - Felicity Wood (Tydskrif vir letterkunde, 2025)
In this article, I explore the spiritual and supernatural aspects of the snake and the ways in which this being has long been associated with various spiritual presences and forces in certain South African belief systems. For instance, Archibald Campbell Jordan’s The Wrath of the Ancestors and some oral narratives from the Eastern Cape province convey positive, benevolent images of the snake as spiritual emissaries, guardians, and guides. Snakes form an integral part of the spiritual order in Eastern Cape cosmology, just as they form part of the ecological balance in the natural world. In the narratives (both written and oral) describing this, the spiritual, the natural world, humans, and other living creatures are interconnected, forming part of a greater whole. More recently, however, as other oral Eastern Cape accounts indicate, snakes have become increasingly connected to sinister aspects of the occult. Oral accounts of the mamlambo, a South African wealth-giving spirit, depict the snake as a malign, sinister supernatural presence bringing about divisions, disparities, and disaster, suggestive of the socio-political, economic, and cultural circumstances that brought belief in the mamlambo and these attitudes towards the snake into being. I discuss Jordan’s novel and oral accounts that convey these contrasting images of the snake and explore the reasons for the changes that perceptions of this being have undergone. In these times of ecological crisis, in this article I highlight the importance of recovering a sense of interconnectedness and integration, and the calamitous consequences of endorsing worldviews characterised by polarisation, imbalances, and inequities.